Nanoarchitectonics of p-type BiSbTe with improved figure of merit via introducing PbTe nanoparticles. Issue 58 (12th November 2021) - Li, Yuanyue; Ren, Mengna; Sun, Zhongsen; Yao, Zhao
Abstract : We introduce 0.5 wt% PbTe nanoparticles into the Bi0.4 Sb1.6 Te3 matrix and possess an ultralow lattice thermal conductivity of 0.26 W m −1 K −1 at 429 K and an excellent ZT value of 1.6 at 482 K as well as a high average ZT ave of 1.38 at 300–500 K. Abstract : Bi0.4 Sb1.6 Te3 (BST) is known to be a unique p-type commercial thermoelectric (TE) alloy used at room temperatures, but its figure of merit ( ZT ) is relatively low for wide industrial applications. To improve its ZT value is vitally important. Here, we show that the incorporation of 0.5 wt% PbTe nanoparticles into BST concurrently causes a large enhancement of power factor (PF) and a significant reduction of lattice thermal conductivity κ L . The increase in PF mainly benefits from the optimization of carrier concentration, maintenance of high carrier mobility and constant rise in Seebeck coefficient. The decrease in κ L can be attributed to the enhanced phonon scattering by the dispersed PbTe nanoparticles and the interfaces between PbTe and the BST matrix by using the Callaway model. Specifically, an ultralow κ L of 0.26 W m −1 K −1 at 429 K is achieved for the composites incorporating 0.5 wt% PbTe nanoinclusions. Consequently, an excellent ZT = 1.6 at 482 K and a high average ZT ave = 1.38 at 300–500 K are achieved, indicating that incorporation of PbTe in BST is an effective approach to improve its thermoelectric performance.